Evaluation of Dislocation Mobility in Wurtzite Semiconductors. Issue 1741 (4th February 2015) - Yonenaga, Ichiro
ABSTRACT: The indentation hardness and yield strength of various wurtzite-structured semiconductors, such as AlN, GaN, InN, and ZnO, were summarized together with those of 6H-SiC. From analysis of the data, the activation energy for motion of an individual dislocation was deduced to be 2–2.7 and 0.7–1.2 eV in GaN and ZnO, respectively, and the evaluated activation energy for dislocation motion showed a dependence on the dislocation energy in the minimum length. The results were evaluated in terms of homology and the basic mechanism of the dislocation process. Dislocation motion is thought to be primarily controlled by the atomic bonding character of the semiconductors.